Eksperimen pendekatan open ended learning berbasis etnomatematika terhadap kemampuan pemecahan masalah matematis siswa ditinjau dari motivasi belajar - Lestari, Sri Lia; Murtiyasa, Budi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The research aims to examining the effect of Open Ended Learning based on Ethnomathematics approach on student’s mathematical problem solving abilities in terms of learning motivation. The research is a part of quantitative research with Quasi Experimental Design. The population is consisting of all 8th grade students of Muhammadiyah 7 Junior High School of Surakarta in the 2022/2023 school year. Two sample classes were taken by Cluster Random Sampling technique. the experimental class which treated with Open Ended Learning based on Ethnomathematic approach and the control class with Open Ended Learning approach. Data collection techniques is using by test, questionnaire, and documentation that analyzed using two-way ANOVA with different cells after proven normality and homogeneity. The result of the research is showing abaout: (1) there are effects of Open Ended Learning approach and Open Ended Learning based on Ethnomathematics approach on student’s mathematical problem solving abilities, (2) there are effects of learning motivation on student’s mathematical problem solving abilities, (3) there’s no interaction between learning approach and learning motivation on student’s mathematical problem solving abilities.